Orientação sexual para jovens adultos com deficiência auditiva - Cursino, Helen Milene (2006)
the study investigated the theme of sexuality among 14 hearing impaired young adults, aged 18 to 35 years, at the Center for Hearing, Language and Visual Disturbances (CEDALVI), a service of the HRAC-USP/Bauru. The aims were: to identify what kinds of information on sexuality were needed; to intervene through a sexual orientation program, so as to inform and discuss themes related to sexuality and to assess the information obtained by means of the sexual education program. To this end, a sexual orientation program was set up with three sessions concerning the following themes: Sexual organs and gender relationships, Caring relationships and Pregnancy, sexually transmitted diseases and self-esteem. Data was collected through a first time questionnaire, with closed true and false questions, with pre and post-tests applied at the beginning and the end of each meeting, followed by interviews to evaluate the whole process at the end of the program. The results showed that most young adults still view the term sexuality as restricted to sexual intercourse or to prevention of sexually transmitted diseases or to contraceptive methods and the media was cited as the main source of information. In the post-test, the greatest number of correct responses occurred for the theme Sexual organs and gender relationships; in general, all participants offered positive reviews for participation in the program. The conclusion was that it is paramount to include sexual orientation in rehabilitation programs, guaranteeing access to information and promoting discussion of such subjects in these young people's lives.